Efektivitas Penerapan Jilid Yanbua Berbasis Smart Book terhadap Pengenalan Huruf Hijaiyah pada Anak Usia 4-5 Tahun di RA Al Iman Banaran - Azizah, Nur; Hasjiandito, Akaat (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the effectiveness of implementing a Yanbua binding version based on a smart book for introducing Hijaiyah letters to children aged 45 years at RA Al Iman Banaran. A quantitative method was employed, using questionnaires administered to 30 children. The Normality Test results indicate that both pretest and posttest data have a significance value of 0.000. Since this significance is less than = 0.05 (0.000 0.05), it shows that the childrens ability to recognize Hijaiyah letters does not follow a normal distribution. The Homogeneity Test results for pretest and posttest in both the experimental class and the control class show a significance value of 0.399. Because this is greater than the significance level , it indicates that the two groups have homogeneous abilities. Based on the Test Statistic table, the Asymptotic Significance (Asymp. Sig.) value is 0.041. Since 0.041 0.05, we reject the null hypothesis (H). Because H is rejected, we conclude that there is a difference in writing and reading abilities between the class without the smart bookbased Yanbua method and the class with the smart bookbased Yanbua method.